2007
DOI: 10.1086/521810
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space TelescopeandSpitzerImaging of Red and Blue Galaxies atz∼ 2.5: A Correlation between Size and Star Formation Activity from Compact Quiescent Galaxies to Extended Star‐forming Galaxies

Abstract: We present HST NICMOS+ACS and Spitzer IRAC+MIPS observations of 41 galaxies at 2 < z < 3:5 in the FIRES MS 1054 field with red and blue rest-frame optical colors. About half of the galaxies are very compact (effective radii r e < 1 kpc) at rest-frame optical wavelengths; the others are extended (1 kpc < r e < 10 kpc). For reference, 1 kpc corresponds to 0.12 00 at z ¼ 2:5 in the adopted cosmology. We separate actively star-forming galaxies from quiescent galaxies by modeling their rest-frame UVYNIR SEDs. The s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
195
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(223 citation statements)
references
References 83 publications
26
195
1
1
Order By: Relevance
“…High-redshift spheroids are much more compact than galaxies of similar mass at z=0 (Daddi et al 2005;Trujillo et al 2006;Toft et al 2007;van Dokkum et al 2008;Cimatti et al 2008). These galaxies with stellar masses of ∼10 11 M ⊙ at z = 1.5 − 2 have typical effective radii of ∼2 kpc, a factor ∼3 smaller than present-day spheroids and a factor ∼2 lower than extended discs with similar mass at the same redshift (Patel et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…High-redshift spheroids are much more compact than galaxies of similar mass at z=0 (Daddi et al 2005;Trujillo et al 2006;Toft et al 2007;van Dokkum et al 2008;Cimatti et al 2008). These galaxies with stellar masses of ∼10 11 M ⊙ at z = 1.5 − 2 have typical effective radii of ∼2 kpc, a factor ∼3 smaller than present-day spheroids and a factor ∼2 lower than extended discs with similar mass at the same redshift (Patel et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Daddi et al 2005;Trujillo et al 2006Trujillo et al , 2007Longhetti et al 2007;Zirm et al 2007;Toft et al 2007;Franx et al 2008;Cimatti et al 2008;Buitrago et al 2008;van der Wel et al 2008van der Wel et al , 2014Bernardi 2009;Damjanov et al 2009;Bezanson et al 2009;Mancini et al 2009Mancini et al , 2010Cassata et al 2011;Damjanov et al 2011;Bruce et al 2012;Szomoru et al 2012;Newman et al 2012;Cassata et al 2013;Belli et al 2014). For example, van der Wel et al (2014) find that the mean effective radius R e of passive galaxies selected with a colour−colour criterion increases as R e ∝ (1 + z) −1.48 over the redshift range 0 < z < 3.…”
Section: Introductionmentioning
confidence: 99%
“…The size evolution appears to be quite dramatic; Toft et al (2007) find that, on average, the quiescent galaxies in their sample z ∼ 2.5 have a factor of 30-40 higher surface density than do red galaxies of the same mass in the Sloan Digital Sky Survey (SDSS).…”
mentioning
confidence: 97%
“…Several recent studies have found evidence that massive galaxies at high redshift are indeed quite compact, particularly those with the lowest estimated star formation rates (Daddi et al 2005;Trujillo et al 2006Trujillo et al , 2007Zirm et al 2007;Toft et al 2007;Longhetti et al 2007;Cimatti et al 2008). The size evolution appears to be quite dramatic; Toft et al (2007) find that, on average, the quiescent galaxies in their sample z ∼ 2.5 have a factor of 30-40 higher surface density than do red galaxies of the same mass in the Sloan Digital Sky Survey (SDSS).…”
mentioning
confidence: 99%